Pengaruh Current Ratio Dan Debt To Equity Ratio Terhadap Return On Assets Pada PT. Wismilak Inti Makmur Tbk Periode 2014-2023 - Melisa Bestiana; Yulian Bayu Ganar (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
The aim of this research is to find out how the financial performance of PT. Wismilak Inti Makmur Tbk for the 2014-2023 period uses the financial reports of PT. Wismilak Inti Makmur Tbk for the 2014-2023 period. This research method uses quantitative methods, the data used is secondary data obtained from the website https://www.wismilak.com/. Data analysis techniques use descriptive statistical tests, normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, multiple linear regression analysis, coefficient of determination analysis, T test, F test using SPSS Version 26 software. The results of this research show partial Current Ratio ( CR) has a negative effect on Return On Assets (ROA) at PT Wismilak Inti Makmur Tbk for the 2014-2023 period. based on partial results, the Debt to Equity Ratio (DER) has no significant effect on Return On Assets at PT. Wismilak Inti Makmur Tbk for the period 2014-2023. Simultaneously, Current Ratio (CR) and Debt To Equity Ratio (DER) have a significant effect on Return On Assets (ROA) at PT Wismilak Inti Makmur Tbk for the 2014-2023 period